2020
DOI: 10.1177/0886260520916282
|View full text |Cite
|
Sign up to set email alerts
|

Rape Myth Acceptance of Police Officers in Portugal

Abstract: This study intended to examine rape myth acceptance (RMA) among police officers and its relationship with sociodemographic data, length of service, specific training in the field, and professional experience with victims of rape. To this end, we applied the Sexual Violence Beliefs Scale (ECVS) and controlled for sociodemographic data, as well as professional experience and specific training in the field, through a self-report questionnaire. The sample was composed of 400 police officers from a city in the nort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 76 publications
1
9
0
Order By: Relevance
“…The training implications could be extended to other professionals involved in supporting survivors of rape, including the police, barristers and judged. This is particularly important given that Fávero et al (2020) found that more senior police officers had higher rates of rape myth acceptance and also considered that is was not necessary to receive specialist training on sexual violence-our research proves otherwise.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…The training implications could be extended to other professionals involved in supporting survivors of rape, including the police, barristers and judged. This is particularly important given that Fávero et al (2020) found that more senior police officers had higher rates of rape myth acceptance and also considered that is was not necessary to receive specialist training on sexual violence-our research proves otherwise.…”
Section: Discussionmentioning
confidence: 68%
“…Walsh et al (2016) found that women who had been drug raped were particularly concerned about not being believed or acknowledgment that what happened to them constituted rape, influenced by often having poor memory about the event themselves, and the lack of a stereotypical rape script of traumatic fear and injury during the rape (Littleton et al, 2006). This concern is justified as Fávero et al (2020) found that older police officers, longer in service, disbelieved that rape was as severe when it did not fit stereotypical representations of rape (e.g. including physical violence).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations